Artificial Intelligence in Business Communication: The Changing Landscape of Research and Teaching. Issue 1 (March 2022) - Getchell, Kristen M.; Carradini, Stephen; Cardon, Peter W.; Fleischmann, Carolin; Ma, Haibing; Aritz, Jolanta; Stapp, James
The rapid, widespread implementation of artificial intelligence technologies in workplaces has implications for business communication. In this article, the authors describe current capabilities, challenges, and concepts related to the adoption and use of artificial intelligence (AI) technologies in business communication. Understanding the abilities and inabilities of AI technologies is critical to using these technologies ethically. The authors offer a proposed research agenda for researchers in business communication concerning topics of implementation, lexicography and grammar, collaboration, design, trust, bias, managerial concerns, tool assessment, and demographics. The authors conclude with some ideas regarding how to teach about AI in the business communication classroom.